Mechanical and morphological properties of different natural fibre reinforced polylactic acid composites: a review - Sherwani, Shah Faisal K.; Sapuan, Salit M.; Leman, Zulkifle; Zainudin, Edi Syams; Abdan, Khalina (Universiti Putra Malaysia Kampus Bintulu Sarawak, 2020)
The determination of mechanical and morphological properties of polylactic acid (PLA) reinforced with different natural fibre were studied in this paper. Tensile, impact, percentage elongation, flexural properties were found out of various composite material like Nettle fibre reinforced PLA, Grewia optiva fibre reinforced PLA, sisal fibre reinforced PLA, composite foams of PLA/bagasse fibre, PLA/flax composites, PLA/ cellulosic natural fibres, Wood fibre reinforced PLA composites. The value of tensile strength was found to be enhanced when compared neat PLA with natural fibre blend PLA. Since PLA is brittle, its nature also changes when natural fibre is applied and the percentage elongations increases as well. Up to 30% improvement in impact strength also noted in previous experiment on different PLA composites. Morphological analysis reveals strong adhesion rates between natural fibre and matrix PLA.